2011
DOI: 10.1007/s10562-011-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decomposition of Methane Over M–Co–Al Catalysts (M = Mg, Ni, Zn, Cu)

Abstract: The catalytic decomposition of methane over M-Co-Al (M = Mg, Ni, Zn, Cu) was studied. The samples were prepared by co-precipitation and characterized by S BET , TGA, DTA, TPR and XRD. The carbon produced in the reaction was characterized by SEM and TPO. Activity tests were carried out in a thermobalance between 500 and 750°C. The results show that the textural properties of the calcined samples did not change significantly with the partial substitution of Co by Mg, Ni, Zn or Cu. On the other hand, there were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 55 publications
(72 reference statements)
2
31
0
Order By: Relevance
“…The latter behaviour depicts a stronger interaction between the Co oxide and the MgO-or CaO-modified support, which requires higher temperatures to be reduced. These results follow the same trend observed for other Mg-CoAl and for CaO-Ni/Al 2 O 3 catalysts with similar loadings for the promoters 14,16,29 . Among the M-Co-Al catalysts, the LaCoAl sample exhibits well-defined behaviour, because both reduction peaks are located at significantly lower temperatures.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The latter behaviour depicts a stronger interaction between the Co oxide and the MgO-or CaO-modified support, which requires higher temperatures to be reduced. These results follow the same trend observed for other Mg-CoAl and for CaO-Ni/Al 2 O 3 catalysts with similar loadings for the promoters 14,16,29 . Among the M-Co-Al catalysts, the LaCoAl sample exhibits well-defined behaviour, because both reduction peaks are located at significantly lower temperatures.…”
Section: Resultssupporting
confidence: 89%
“…Amorphous carbon oxidises at approximately 400°C, while the DTA peaks in Figure 8 are centred at ca. 490°C, which could be assigned to carbon nanotubes or nanofibres 27,29,42 . Therefore, the TPO/DTA analysis suggests that filamentous carbon is formed for the Co-Al samples investigated herein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active and stable catalysts for biogas reforming are mostly noble metals, such as rhodium, palladium, iridium, platinum and ruthenium [38] besides inexpensive nickel which, however, is very active to coke deposition [39]. On the other hand, the addition of other metal, such as platinum, palladium, cobalt, molybdenum and copper can improve the catalytic performance of nickel [40,41]. Aiming to obtain active and stable catalysts for producing hydrogen from biogas, catalysts based on nickel and copper supported on aluminum and magnesium oxides were studied in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported on methane to carbon nanotubes or nanoparticles decomposition over cobalt contained catalysts [8,9], but to the best of our knowledge, there is no information on nanotubes filled with continuous cobalt nanowires prepared from methane.…”
Section: Introductionmentioning
confidence: 99%